(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Biological enzyme is a kind of substance, which can catalyze specific reaction. In our work, sericin membranes are prepared under the catalysis of tyrosinase, which promoting protein molecules crosslinking through tape casting method. Taking the water solubility of sericin membranes as the evaluation index, the optimal preparation conditions are determined as follows: the dosage of tyrosinase 1000 U/g, the reaction temperature 45 00b0C, for 90 min, 2% glycerol and drying temperature at 45 00b0C. The results of infrared spectra indicate that the structure of amide I is changed in crosslinked sericin membranes. The XPS results indicate the O atom content is increased in crosslinked sericin membrane. This verifies the crosslinking of sericin protein by tyrosinase.